Trade fairs as promotional tool for IPA members - Maravillosa, Leah F. (2007)
The study investigated the existing policies governing the management of trade fairs and how were trade fairs organized by the Ilonggo Producers Association are managed. Appropriate measures to improve management of trade fairs as well as strategies to improve business of IPA member SMEs are suggested and recommended. A total of 21 respondents who are member SMEs located within the immediate area of Iloilo City are selected to answer the survey questionnaire prepared by the researchers. Descriptive statistics is used to analyze the results of the survey related to the effectivity of trade fairs as used by the Ilonggo Producers Association to promote its members. The review and analysis of the survey showed that member SMEs are quite aware f the regulations implemented by the Ilonggo Producers Association and had enumerated quite a few policies that they are aware of currently. These regulations or policies are also well implemented and respondents cited a handful of measures by which these policies are followed. These trade fair regulations also made the trade fairs successful but problems are also present. A large percentage of respondents indicated that the high cost of booth rentals prevents them from joining trade fairs organized by the Ilonggo Producers Association and suggestions to resolve the identified problems were also made by the respondents. Overall, respondents replied that IPA organized trade fairs are well organized. There is proper coordination between trade fairs participants and the management of the trade fair as well as venue. Forty three percennt of the respondents indicated that there is satisfactory coordination between participants and management. Adequate management of trade fairs is rate as satisfactory by the respondents also. A big percentage of member SMEs of the Ilonggo Producers Association had been joining trade fairs for one to three years whose main reason is to increase sales. However, increase in sales attributed to trade fairs is only one to five percent of the total annual sales of the member SMEs. It only shows that trade fairs are not an effective tool to promote member SMEs since only a small percentage in sales can be credited to it. The study recommended implementation of policies and strategies to boost membership as well as effectivity of the Ilonggo Producers Association in promoting its membership. The first recommendation being a policy that will ensure the attendance or participation of member SMEs in IPA organized trade fairs that will promote greater product selectivity of consumers. The second recommendation is the maintenance of a databank for each member for periodic assessment of sales growth, improvement and development on product quality, and business management of member SMEs. The third policy recommendation is the creation of a policy that will link IPA with several cultural festivities around the region. Strategy recommendations of the researchers included he maintenance of a website highlighting the various products as well as the database for member SMEs of the Ilonggo producers Association. Post trade evaluation is also recommended so as the organization will be aware of the problems that its members are experiencing every after trade fair or program conducted. A comparison of the sales or profit earned from previous trade fairs can also help the Ilonggo Producers Association as well as its member SMEs pinpoint key areas in its management and programs that needs revision or make programs that can be helpful to the operation of both parties. It is further suggested by the researchers that a criteria for selecting the personnel to man trade fairs be established especially in the case of common selling to separate personal interests from that of the IPA. This is in case of members of the management of the Ilonggo Producers Association to delete bias in common selling. The conduct of this study also uprooted some issues and problems that can be studied further such as the high rate of decrease in member SMEs of the Ilonggo Producers Association and also a study that will investigate the significance of member benefits to that of membership in the IPA.
Research Paper (Mgt 299 - Research Methods in Management). -- Iloilo City : UPV-CM, February 2007.